Thermal Performance Analysis Of TiO₂ and Paraffin as Phase Change Materials - I Made Arsawan; IDG Ary Subagia; I KG Wirawan; DNK Putra Negara; NW Sugiarti (Logic : Jurnal Rancang Bangun dan Teknologi, 2025)
Phase change materials (PCMs) are materials that can store and release thermal energy through phase changes from solid to liquid at specific temperatures. This study aims to analyze the effect of TiO₂ concentration in paraffin as a phase change material for thermal energy storage applications. TiO₂ is used as an additive to paraffin to enhance thermal conductivity and accelerate heat transfer, thus improving the performance of the phase change material (PCM). This research investigates the thermal characteristics of the paraffin and TiO₂ mixture by measuring thermal properties such as melting point, heat capacity, thermal stability, and the energy storage capability of the material using techniques such as Differential Scanning Calorimetry (DSC). The results show that the addition of TiO₂ can enhance the thermal performance of pure paraffin as a phase change material. A concentration of 10% TiO₂ can absorb thermal energy up to 94.58 kJ/kg. This study is expected to contribute to the development of more efficient energy storage materials.